A secondary research on human endocrine physiology in the Al-Qur’an and the ahadith - Abdul Ghani, Radiah; Ikmal Hisham, Ahmad Irfan; Ahmad Rosli, Athirah Nur (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
Physiology is one of the remarkable branches in medical field which allows an appreciation of the anatomy as well as the functions of being; which then gives an idea on the purpose of a creation and a better understanding of the purpose of humans themselves. However, modern physiology taught in many Westernised textbooks lack the link and reflection to the worldview of Islam. As a result of this divorce between the modern physiology and the religious worldview, physiology as a subject is lacking “spiritual” connection and thus, produces students with lack of connection with the Tawhidic (Oneness) and admirableness to Allah, much to the dismay of the Islamic teaching. Thus, this paper is aimed to review the relevant scientific knowledge in endocrine physiology and relate it with the Qur’anic verses and Hadith. The roles of melatonin and cortisol that changes between day and night, the role of touch and the release of oxytocin are explained from the Islamic perspective based on the relevant Qur’anic verses and/or the Ahadith. Future research in integrating the physiology with the evidence from the Qur’an and the Ahadith should be attempted by medical and biomedical scientists alike, to further enhance and develop the concept of physiology as a subject in medical schools, not limited to the physical sciences per se, but also the spiritual and metaphysical dimensions.